Investigating the efficacy of culturally specific academic literacy and academic honesty resources for Chinese students : final project report. - Whitelaw, Paul A.; Henderson, Fiona; Jose, Penny; Defeng, Li; Cuiming, Gao; Wenjie, Shi; Qinxi, Li (Victoria University, 2010)
Academic literacy and plagiarism policies within most universities tend to be overly textual and punitive; written by academics for academics. Many remedial and support systems for students tend to be overly prescriptive and procedural and don't appear to do enough to encourage the development of academic literacy and academic honesty, especially for those students from a non English speaking, non western academic background such as Chinese students. This project was designed to develop a clear understanding of the efficacy and efficiency of messages and media that best convey the key themes of academic literacy and academic honesty to Chinese students. The project uses and advances existing national and international knowledge particularly regarding teaching and learning of academic literacy and honesty to international students in Australia and the use of multimedia tools to assist understanding and adoption. The project found that although Chinese students generally think they understand the concepts of academic honesty and plagiarism, they are not an homogeneous group. They have their own individual difficulties applying the concepts in an environment where the expectations to study independently, think critically and reference widely are different from those to which they are accustomed at home. Language difficulties, loneliness, homesickness and cultural differences further compound their problems. [p.7, ed]